CP-113 Evaluation of professional practices about the central venous catheter management in a surgical cardiovascular intensive care unit: between theory and practice. (25th February 2017) - Fenoy, T; Lefebvre, M; Genay, S; Leroy, G; Robin, E; Décaudin, B; Odou, P
Abstract : Background: Use of a central venous catheter( CVC) line is associated with a high risk of infections and complex infusion requirements. Evaluation of professional practices(EPP) is a useful tool in a process of quality improvement and risk management. Purpose: Our aim was to assess the differences between user knowledge and practice concerning management of a CVC. Material and methods: This was a preliminary prospective study in a surgical cardiovascular intensive care unit(ICU) in July 2016. Data were collected by direct observations of CVC settings and standardised interviews with nurses. We focused on the four items in common between the observational study and the answers given by nurses: dressing changes, unused lines management, use of CVC line for blood sample and infusion lines management. Results: We observed 61/134 infusion lines and interviewed 31/61 nurses. 100% of nurses declared changing dressings when they becomes loosened or soiled. Only 62% of the dressings had a good performance (29.5% loosened ±19.7% soiled ±11.5% lightly covered) during the observational study. This may have been due to the jugular position of the CVC and the high temperatures in July. 6% of nurses thought the unused lines of the CVC should be equipped with keep vein open infusion and 94% said it should be left with anything. In practice, only 11% were left free and a device was connected in 89%. No keep vein open infusion was observed. 100% of nurses said they performed blood samples on CVC and 100% agreed to flush the infusion line after sampling. In practice, 34% of the lines were soiled (sign of poor or no flushing). This can be explained by the need for a high number of samples. 97% of nurses claimed that catecholamines should be infused alone on the proximal line. 78% were well connected with 50% alone. 50% were infused alone with 22% on another line to avoid haemodynamic disturbances because of different infusion rates. Conclusion: The team seemed to have the knowledge but due to hard working conditions in the ICU, we found divergent results. Despite discrepancies between the two parts of the EPP, a multidisciplinary team of nurses, pharmacists and doctors should propose corrective action and support changes in technique solutions and training in performing changes. No conflict of interest